The effect of terrorist attacks on attitudes and its duration - Chadefaux, Thomas (My University, 2023)
Is terrorism effective as a tool of political influence? In particular, do terrorists succeed in affecting their targets’ attitudes, and how long does the effect last? Existing research unfortunately is either limited to small samples or does not address two main difficulties: issues of endogeneity and the inability to assess the duration of the effect. Here, we first exploit the exogeneity to the selection process of the success or failure of an attack as an identification mechanism. Second, we take advantage of the random allocation of survey respondents to interview times to estimate the duration of the impact of terrorist events on attitudes. Using survey data from 30 European democracies between 2002 and 2017, we find first that terrorism affects people's reported life satisfaction and happiness—a proxy for the cost of terrorism in terms of utility. However, we also find that terrorist attacks do not affect respondents’ attitude toward their government, institutions, or immigrants. This suggests that terrorism is ineffective at translating discontent into political pressure. Importantly, we also find that all effects disappear within less than two weeks.
PUBLISHED
Keywords: Survey methodology; Terrorism; Political attitudes; International Integration